2016
DOI: 10.3139/146.111415
|View full text |Cite
|
Sign up to set email alerts
|

A metastable phase diagram for the dynamic transformation of austenite at temperatures above the Ae3

Abstract: A metastable phase diagram for the dynamic transformation of austenite at temperatures above the Ae 3 A method is proposed for calculation of the pseudobinary phase diagram associated with the dynamic transformation of austenite to ferrite. Here the driving force is taken as the difference between the austenite flow stress at the moment of initiation and the yield stress of the fresh Widmanstätten ferrite that takes its place. The energy opposing the transformation consists of the Gibbs energy difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The present analysis is focused on a steel with 0.06 wt % C, 0.3 wt % Mn and 0.01 wt % Si with a paraequilibrium Ae 3 temperature of 870 • C. Note that this is similar to the material used in previous investigations by the present authors [4,6,12,[15][16][17]. Hot compression tests were performed on a 100 kN MTS machine (MTS, Eden Prairie, MN, USA) equipped with a radiation furnace and a temperature controller.…”
Section: Methodsmentioning
confidence: 99%
“…The present analysis is focused on a steel with 0.06 wt % C, 0.3 wt % Mn and 0.01 wt % Si with a paraequilibrium Ae 3 temperature of 870 • C. Note that this is similar to the material used in previous investigations by the present authors [4,6,12,[15][16][17]. Hot compression tests were performed on a 100 kN MTS machine (MTS, Eden Prairie, MN, USA) equipped with a radiation furnace and a temperature controller.…”
Section: Methodsmentioning
confidence: 99%
“…Such ferrite forms displacively when the driving force for DT overcomes the total obstacle, which consists of the free energy difference between the phases as well as the lattice dilatation work and shear accommodation work. 7,8) The amounts of ferrite formed and retained were reduced by about 0.3, 1.2, 2.9, 4.2, 4.8 and 5.5% per pass on the second, third, fourth, fifth, sixth and seventh, respectively, when the interpass time was increased by 20 s. This is because longer interpass times favor the retransformation of ferrite back into austenite. Static retransformation takes place because the Gibbs energy of ferrite is higher than that of the austenite in this temperature range.…”
Section: Production/retention Tendencies For Ferrite Transformationmentioning
confidence: 95%
“…Concurrently, as the Ae 3 temperature is approached, there is a reduction in the height of the obstacle to the transformation. 7,8) The effect of increasing the length of the interpass interval is in turn associated with reducing the retained strain through static recovery.…”
Section: )mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This has been shown to occur throughout the austenite phase field. 8,9) In earlier publications, the present authors have reported that the amounts of ferrite formed per pass increase with decreasing temperature. 9,10) Subsequently, the metastable ferrite tends to retransform to austenite to an extent that increases with the length of the interpass interval.…”
Section: Introductionmentioning
confidence: 95%
“…1) Although some studies regarding the retransformation of ferrite into austenite during holding have already been published, 1,8,10,12) these have been limited to isothermal and single pass conditions. Here this phenomenon is explored under continuous cooling and multiple pass conditions, which are closer to those applicable to industry.…”
Section: 245)mentioning
confidence: 99%